Neonatal haemostatic parameters in correlation to gestational age and birth weight. (11th July 2022) - Mitsiakos, Georgios; Katsaras, Georgios N.; Pouliakis, Abraham; Papadakis, Emmanouil; Chatziioannidis, Ilias; Mitsiakou, Christina; Gialamprinou, Dimitra; Papacharalampous, Efthimia; Kioumi, Anna; Athanasiou, Miranda; Athanassiadou, Fani; Sfoungaris, Dimitrios; et al.
Abstract: Introduction: The aim of our study was to establish reference ranges for neonatal coagulation and fibrinolysis parameters and to investigate their relationship with gestational age (GA) and birth weight (BW). Methods: A single‐centre prospective study was conducted in all healthy neonates born in our hospital during the study period, excluding those with maternal or neonatal disorders and diseases that affect haemostasis. The following parameters were measured: fibrinogen, prothrombin time (PT), international normalized ratio (INR), activated partial thromboplastin time (aPTT) as well as factors II, V, VII, VIII, IX, X, XI and XII, von Willebrand (vWF), protein C, free protein S, antithrombin (AT), activated protein C resistance (APCr), tissue plasminogen activator (tPA) and plasminogen activator inhibitor‐1 (PAI‐1). Results: Study population consisted of 327 neonates. Fibrinogen, AT III, proteins C and S, PAI‐1, vWF and factors II, V, VIII, IX, XI and XII were positively correlated, while PT, aPPT, INR, APCr and tPA were negatively correlated with GA and BW. Proteins C and S, factors II, VIII, IX, XI and vWF, as well AT III and PAI‐1 had a significant positive linear correlation with GA, while aPTT had a significant negative one. Fibrinogen, and factors V, VII and XII had a significant positive linear correlation with BW, while factor VIII, tPA, as well PT and INR had a significant negative one. Conclusion: Fibrinogen, AT III, proteins C and S, PAI‐1, vWF and factors II, V, VIII, IX, XI and XII increase with GA and BW.